Network centrality analysis in management and accounting sciences. Issue 2 (8th January 2020) - Dias, Alexandre; Ruthes, Sidarta; Lima, Leonardo; Campra, Elisa; Silva, Maycon; Bragança de Sousa, Millena; Porto, Geciane
Abstract : Purpose: This study aims to analyze how gender, research experience and geography are related to the researchers' importance in the co-authorship network on management and accounting in Brazil. Design/methodology/approach: A social network based on the co-authorship relationships in the papers published in leading Brazilian journals was examined using a logit model to estimate the probability of occupying prevailing positions. Findings: The findings showed a network with a high level of fragmentation and a scarcity of authors serving as gatekeepers. Based on the number of directed links and collaboration with influential and well-connected authors, men were more likely to occupy central positions than women. Authors with higher academic degrees tended to establish more links but were more likely to distance from other authors. In terms of geography, authors from more- and less-favored regions may report similar propensity to occupy central positions. Practical implications: Decision-makers should consider the importance of strengthening collaboration between different research groups and encourage female participation in broader collaborative networks. Research evaluation bodies should strengthen incentives regarding interinstitutional partnerships. Originality/value: Studies on collaborative networks in management and accounting sciences are less common and generally focus on describing the networks. This paper combines social network analysis and econometric procedures to analyze the relationship between demographic and geographical aspects, and distinct network centrality indexes.